Creativity and Innovation of the Community Based on Plastic Waste in Ubung Kaja Village, Bali - JAYAWARSA, A.A Ketut; LAKSMI, Putu Ayu Sita (Community Services: Sustainability Development, 2024)
This community service activity aims to reduce the abundance of plastic waste, particularly plastic bottles, in the Ubung Kaja Village environment. After participating in this activity, participants will learn how to make chairs from used plastic bottles and process plastic waste, making the resulting products marketable. One of the efforts to tackle non-organic waste (such as plastic bottles and plastic bags) is to create chairs, tables, and beds with high market value. The aim and benefit of this community activity is to develop appropriate technology for managing plastic and bottle waste, thereby reducing the increasing volume of plastic waste. Ecobricks, commonly known as environmentally friendly bricks, are a method to minimize waste by filling plastic bottles with non-organic waste until they are completely solid and compact. This practice also educates children about non-organic waste, demonstrating how it can be repurposed into useful items like tables or chairs instead of waste.